Pricing strategy and its implication on hotel financial performance / Wan Ahmad Nasroun Wan Salman - Wan Salman, Wan Ahmad Nasroun (2010)
The major issues that affect a firm's revenue is to get the price right. Price plays an important role since it is one of the strategic marketing variables that have direct impact on sales revenue or financial performance. However, the studies of pricing within the marketing discipline were very few particularly in hotel industry. This study was to ascertain the implications of hotel room pricing strategies adopted by 5 star-rating hotels in Malaysia with regards to their financial performance. Apart from that, this study was also aimed to examine the relationship between hotel pricing strategy, financial performance and external environment as moderating variable. The pricing strategies construct were derived from various articles on pricing in services industry and integrated according to four dimensional measures of cost-based, competitive, differential and psychological pricing strategy. Meanwhile, financial performance was measured by means of average room rate (ARR), occupancy percentage and revenue per available rooms (RevPAR). Samples for this study comprised of 72 hotels (5-star) with 100 rooms and above throughout Malaysia in which hotel manager was selected as a respondent. The statistical analyses used involved Multiple Regression, Hierarchical Regression and Moderated Regression analysis. Results indicated that cost-based pricing and differential pricing have a negative relationship with hotel financial performance, whereas competitive pricing and prestige pricing showed a positive relationship. This supported the notion that, for example; when a hotel that used cost-based pricing increased their room rates, it will lead to decrease in their financial performance or vice versa. Generally, the relationship between pricing strategy and financial performance were supported since the overall model showed that it was significant. Overall, the proper selection of pricing strategy by the hotel managers may lead the organization to their targeted revenue or income. Furthermore, it would also profitable for a hotel organization to implement more than one pricing strategy in their marketing strategy.